(untitled) (Studia Prawnicze / The Legal Studies, 2023)
The paper is an attempt at analysing how the actual legislative process bears upon the role the Sejm plays there and the execution of its competence. Availing of ceratin assumptions of the theory of decision the author has pointed to the fact that the decision-making process (and the legislative process as well) is always the process of data-processing. Therefore, futheron the paper deals with the problem of information indispensable to the Sejm to make legislative decisions. Having made an attempt to ascertain with what information the organ can and should be furnished, both in terms of subject matter (point I) and form (point II), the author has come to the following general conclusions: — the distinction should be made into particular aspects of the guiding state decisions: the axiological (political), praxiological (expert) and social one; — in its work the Sejm should lay the strongest stress on the social aspect of the discussed bills; — in the legislative process the Sejm is to formulate the social aspect in an authoritative manner and confront the former with expert assessment of the administration, finally to exert supervision over the correct approach to both axiological and praxiological aspects of the discussed bills; — The required amount of expertise on the part of the deputies can be reduced when the social aspect of the resolution is to be formulated; — this information is substantial and indispensable which would enable the Sejm to make a final selection among at least two variants of a resolution that have been formulated either by the organ which is the author of the respective bill or by the Sejm, on the basis of the information it previously had or received; — the information the Sejm is provided with should be synthetizing, clear, true and quickly purveyed, selected among fragmentary, uncertain and detailed materials; — moreover the deputies should have an opportunity to obtain more detailed documentation at any request. The analysis of the actual operation of the Sejm (point III) has pointed out that it is not provided with information that meets the above requirements. This results in the situation when the legislature depends on the organs which submit their bills. In the final part of the paper (point IV) the author has discussed in brief those limitations of the role the Sejm plays in the legislative process which are of political nature. E.g. those which hinder the deputies from far reaching motions relating to the subject matter rather than stylistic or editorial aspects of the bills. It seems that this is due to the conviction which is common among the deputies, that the bills submitted by the Council of Ministers have already been aproved by the top party authorities.